2022
DOI: 10.3389/fphar.2021.775126
|View full text |Cite
|
Sign up to set email alerts
|

New Oral Anticoagulants for Venous Thromboembolism Prophylaxis in Total Hip and Knee Arthroplasty: A Systematic Review and Network Meta-Analysis

Abstract: Background: There is controversy over whether use of new oral anticoagulants (NOACs) associates with increased hemorrhage risk compared with non-NOAC. Meanwhile, determining which NOAC to use remains unclear. We aimed to summarize the evidence about NOACs in venous thromboembolism (VTE) prevention for patients with total hip and knee arthroplasty (THA and TKA).Methods: We searched RCTs assessing NOACs for VTE prophylaxis in adults undergoing THA and TKA in Medline, Embase, and Cochrane up to May 2021. Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Hemorrhage events mostly occurred with anticoagulation therapy. In previous studies, approximately 17.24% of patients experienced bleeding events after treatment with rivaroxaban 14 . In elderly patients, certain comorbidities (renal insufficiency in particular) were more commonly affected by rivaroxaban pharmacokinetics and pharmacodynamics.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Hemorrhage events mostly occurred with anticoagulation therapy. In previous studies, approximately 17.24% of patients experienced bleeding events after treatment with rivaroxaban 14 . In elderly patients, certain comorbidities (renal insufficiency in particular) were more commonly affected by rivaroxaban pharmacokinetics and pharmacodynamics.…”
mentioning
confidence: 88%
“…In previous studies, approximately 17.24% of patients experienced bleeding events after treatment with rivaroxaban. 14 In elderly patients, certain comorbidities (renal insufficiency in particular) were more commonly affected by rivaroxaban pharmacokinetics and pharmacodynamics. Recent studies conducted in Korea and Japan demonstrated that lowdose rivaroxaban was associated with a lower risk of hemorrhage and all-cause mortality in the management of patients with nonvalvular atrial fibrillation.…”
mentioning
confidence: 99%
“…Evidence shows that NOACs exert more clinical benefits without increase in hemorrhage in Total Hip and Knee Arthroplasty compared with traditional non-NOACs. 7 Mechanical prophylaxis (eg, antiembolism stockings or intermittent pneumatic compression) can be provided to the hospitalized patients in whom pharmacological prophylaxis is contraindicated, and they as well should be extended until the patient is adequately able to walk. 8 Evidence supports that all hospitalized patients should be counselled about the risk factors and consequences of VTE, the adverse effects of thromboprophylaxis medications, and the appropriate risk-reduction modalities prior to initiating thromboprophylaxis.…”
Section: Introductionmentioning
confidence: 99%
“…20 Prior systematic reviews and meta-analyses have investigated pharmacological thromboprophylaxis in smaller patient populations or intervention groups with unspecified treatment details. While other analyses have found that rivaroxaban was associated with the greatest reduction in deep vein thrombosis (DVT), they were limited by the patient population (only TKAs 27 ), or by interventions (comparisons between NOACs and non-NOACs unclear 28 ; exclusion of important interventions including aspirin, apixaban, edoxaban 29 ). These analyses included a small number of randomized controlled trials (RCTs) 30,31 and included studies which report on doses or regimens of medications which fall outside of current treatment guidelines, which limits the applicability of their results.…”
mentioning
confidence: 99%